Enhancing Vocabulary Mastery in Narrative Text through Wordwall Game - Ambar Nur Aisiyah, Almadani; Mulyadi, Dodi; Budiastuti, Riana Eka; Wijayatiningsih, Testiana; Singh, Charanjit Kaur Swaran (ETERNAL (English Teaching Journal), 2024)
Enhancing vocabulary mastery through the Wordwall game is important because students often face several common difficulties in mastering English vocabulary, such as lack of engagement, limited exposure to new words, and difficulty in retaining vocabulary. This study aims to answer whether the use of the Wordwall game can improve eighth-grade students' English vocabulary mastery. Classroom action research was conducted using four stages: planning, acting, observing, and reflecting. Data were gathered via observation, questionnaires, and testing. The study revealed that integrating the Wordwall game enhanced vocabulary proficiency and increased motivation among students in their English language acquisition. The game stimulated students' comprehension and retention of relevant vocabulary, fostering their enthusiasm for acquiring English. In addition, there was a notable improvement in students' proficiency in vocabulary. The study showed that students who used the Wordwall game had higher vocabulary test scores compared to before using the game. This study provides evidence that students have attained favorable learning outcomes and exhibit high levels of motivation to expand their vocabulary through the Wordwall game. They recognized that the Wordwall game was beneficial in facilitating their acquisition of English vocabulary. It is recommended that teachers use this strategy and regularly evaluate teaching techniques.